Negative life events in childhood as risk indicators of labour market participation in young adulthood: a prospective birth cohort study. - Thomas Lund (Public Library of Science (PLoS), 2013)
Background Most previous studies on reliance on social benefits have focused on health, sickness absence, work environment and socioeconomic status in adulthood. Extending the focus to include early life circumstances may improve our understanding of processes leading to educational and occupational marginalisation and exclusion. The aim of this study was to investigate if multiple negative life events in childhood determined future labour market participation, and to identify important negative life events for labour market participation in young adulthood. Methods Of a cohort of 3,681 born in 1989 in the county of Ringkjoebing, Denmark, 3,058 (83%) completed a questionnaire in 2004. They were followed in a register on social benefits for 12 months in 2010-2011. Logistic regression analyses were used to investigate associations between negative life events in childhood and future labour market participation, taking into account effects of socio-economic position, school performance, educational plans, vocational expectations and general health. Results A total of 17.1% (19.9% males, 14.4% females) received social benefits for at least 4 weeks during follow-up. Labour market participation decreased with number of negative life events, especially for females: Females who had experienced their parents' divorce, had been abused, or had witnessed a violent event, showed decreased labour market participation, when adjusting for SES, school performance, educational plans, vocational expectations and general health at baseline. Attributable fractions ranged from 2.4% (parents' alcohol/drug abuse) to 16.1% (parents' divorce) for women. For men, risk estimates were lower and insignificant in the most adjusted models. Attributable fractions ranged from 1.0% (parents' alcohol/drug abuse) to 4.9% for witnessing a violent event. Conclusions Information on childhood conditions may increase the understanding of determinants of labour market participation for young adults. Knowledge of negative life events in childhood should be taken into account when considering determinants of labour market participation and identifying high-risk groups.